2022
DOI: 10.1007/s10864-022-09486-1
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Virtual Positive Behavior Support in a Special School for Students with ASD

Abstract: In response to the demand for adopting a social justice system to manage students’ challenging behaviors, many countries are implementing positive behavior support (PBS) programs at the school level. However, the use of PBS in Saudi Arabian schools is still a goal rather than reality. It is strongly evident that school-wide PBS can be applicable to different educational contexts. Therefore, the purpose of this study was to evaluate the efficacy of a virtual school-wide positive behavior support program for stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Four of these studies were rated as high‐quality, with two interventions well described (Gobrial, 2017; Tounsi et al, 2022) and two studies having an acceptable level of intervention reporting (Abdel Raheem et al, 2010; Al‐Ajami & Al‐Nwaiser, 2016). Karima's (2017) and Alwahbi's (2022) studies were rated as medium quality, and the interventions were well‐reported.…”
Section: Resultsmentioning
confidence: 99%
“…Four of these studies were rated as high‐quality, with two interventions well described (Gobrial, 2017; Tounsi et al, 2022) and two studies having an acceptable level of intervention reporting (Abdel Raheem et al, 2010; Al‐Ajami & Al‐Nwaiser, 2016). Karima's (2017) and Alwahbi's (2022) studies were rated as medium quality, and the interventions were well‐reported.…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing meta-analysis, Van Camp et al (2020) 2022) conducted a meta-analysis to determine the characteristics of the model of preschool MTSS, its effectiveness across diverse conditions, and its applicability to various populations. Alwahbi (2022) analyzed the effectiveness of using PBS for students with Autism Spectrum Disorders in special education schools using meta-analysis. Over the past half-decade, many studies have used meta-analysis to demonstrate the effectiveness of PBS (Hirsch et al, 2020;Radley et al, 2023;Smith, George, & Prado, 2017).…”
Section: ) Keyword Clustering Analysismentioning
confidence: 99%